Plethora of benefits on cloud accounting services / Nor Kartini Mohd Rodzi - Mohd Rodzi, Nor Kartini (Fakulti Perakaunan, 2023)
The world of accounting software is rapidly shifting towards cloud computing. The accounting software vendors have moved their products to the cloud and provide different forms of cloud accounting solutions This integration of basic cloud computing principles and activities carried out by accounting software companies has led to the development and popularity of cloud accounting solutions. These solutions offer many benefits, including increased accessibility, scalability, and cost efficiency, making them an attractive option for many businesses (Motalo, 2023). Cloud accounting is an "online accounting service" that runs on the servers and accessibility is using the web browser, over the Internet and it serves the same function as accounting software installed on a computer (Sutthikun, Thapo & Sahayrak, 2018